2015
DOI: 10.17700/jai.2015.6.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Access and Usage of ICTs for Agriculture and Rural Development by the tribal farmers in Meghalaya State of North-East India

Abstract: A B S T R A C TA study was conducted to find out the level of access and usage of ICTs among farmers of Meghalaya state of India. A total of 120 farmers were randomly selected for the study during November 2013 to May 2014. The results showed that majority of the farmers owned mobile phones as well as television and radio. The most frequently used ICT was mobile phone. Mobile phones were widely used by the farmers for social communication, contacting middle men for the marketing of produce and contacting exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 11 publications
12
47
1
Order By: Relevance
“…They made an argument that pertinent to extensive use of ICTs they had more information and knowledge about the latest and site-specific technologies of farming. Similar results were reported by the Syiem & Raj (2015) as farmers' knowledge regarding availability and accessibility of inputs, diseases management and crop management escalated due to ICTs use. Sharma et al (2012) cemented an increased penetration of ICTs among farmers to uptake agricultural technologies.…”
Section: Knowledge and Skill Level Of Respondents Regarding The Use Osupporting
confidence: 81%
See 1 more Smart Citation
“…They made an argument that pertinent to extensive use of ICTs they had more information and knowledge about the latest and site-specific technologies of farming. Similar results were reported by the Syiem & Raj (2015) as farmers' knowledge regarding availability and accessibility of inputs, diseases management and crop management escalated due to ICTs use. Sharma et al (2012) cemented an increased penetration of ICTs among farmers to uptake agricultural technologies.…”
Section: Knowledge and Skill Level Of Respondents Regarding The Use Osupporting
confidence: 81%
“…The size of land holding in rural areas predicts the level of income of farmer (Ojo & Babayo, 2013;Pervaiz et al, 2013). The results reported by the Syiem & Raj (2015) found a significant relationship of income of farmers with the use of ICTs.…”
Section: Knowledge and Skill Level Of Respondents Regarding The Use Omentioning
confidence: 90%
“…However, Mittal et al (2012) have also noted that asymmetric and old information, and lack of use of local language in ICT tools, which has no correlation, and do no work closely with farmers. This study partially agrees with author (Syiem & Raj, 2015) that use of a particular type of ICT tool depends more on economic condition of farmers and education level. It was the main purpose of the paper to draw attention on utilization of ICT tools by local smallholder farmers, trader and seller; and the present government and private institutes need to establish the ICT informatics center in every district of India by focusing over farmer needs, local language, demand of particular areas and the upcoming problems in adopting the ICT, then obviously this would help the farmers and increase the use of ICTs amongst the farming community to large extent.…”
Section: Development Of the Food Traceability System In Indiasupporting
confidence: 91%
“…Both categories of extension officials perceived high cost of some parts of ICT tools or maintenance as a barrier to their adoption. Similarly, Syiem and Raj (2015) reported lack of confidence in operating ICT tools, erratic power supply, low network connectivity and cost of repair as constraints. Omotesho et al (2012) also reported a number of challenges that were serious constraints to access of ICTs among Agricultural Extension Officers and Subject Matter Specialists in Kwara State, Nigeria.…”
Section: Constraints To the Use Of Ictmentioning
confidence: 99%